2007
DOI: 10.1037/0096-3445.136.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Color and psychological functioning: The effect of red on performance attainment.

Abstract: This research focuses on the relation between color and psychological functioning, specifically, that between red and performance attainment. Red is hypothesized to impair performance on achievement tasks, because red is associated with the danger of failure in achievement contexts and evokes avoidance motivation. Four experiments demonstrate that the brief perception of red prior to an important test (e.g., an IQ test) impairs performance, and this effect appears to take place outside of participants' conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
593
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 554 publications
(628 citation statements)
references
References 101 publications
24
593
2
9
Order By: Relevance
“…After completing the perceptual task, participants performed an anagram task to measure goal striving. Successful performance on anagram tasks is a common measure of goal pursuit in social psychological studies of achievement (e.g., Bargh et al, 2001; Elliott et al, 2007; Shah, 2003); performance tends to correlate highly with persistence but has the advantage of also tapping into how much effort participants expend, and how well they concentrate, two other markers of goal-driven behavior.…”
Section: Methodsmentioning
confidence: 99%
“…After completing the perceptual task, participants performed an anagram task to measure goal striving. Successful performance on anagram tasks is a common measure of goal pursuit in social psychological studies of achievement (e.g., Bargh et al, 2001; Elliott et al, 2007; Shah, 2003); performance tends to correlate highly with persistence but has the advantage of also tapping into how much effort participants expend, and how well they concentrate, two other markers of goal-driven behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, other research showed the interior environments with cool colours (i.e. blue and green) have poorer task performance [10,19].…”
Section: Discussionmentioning
confidence: 99%
“…white, red, blue and green) affect task performance [5,6,7]. Some studies pointed out, compared to blue and green offices, employers performed better in white and red offices [8,9], while other studies showed dissimilar results [10].…”
Section: Introductionmentioning
confidence: 99%
“…Let the warning (Cervical Spine Stress) level be λ and the angle at which the phone is inclined be φ from Y-axis and the magnitude of the vector of the value of Z-axis be A γ and Y-axis be A β then: Above, Figure 5 is portrayal of a "Very Serious" Heads Up notification in Android Nougat when the posture should be immediately corrected. Red is often associated with warning and seriousness [12]. The color grades shift to more soothing as the notification type decreases.…”
Section: The Algorithmmentioning
confidence: 99%